2017
DOI: 10.1002/admi.201700121
|View full text |Cite
|
Sign up to set email alerts
|

Active Control over the Wettability from Superhydrophobic to Superhydrophilic by Electrochemically Altering the Oxidation State in a Low Voltage Range

Abstract: Fast and reversible active control over the surface wettability of electrodeposited copper is achieved through electrochemical manipulation of the oxidation state. The switchable wettability described in this work allows for facile and precise control over the surface wettability, ranging from superhydrophobic (contact angle about 157°) to superhydrophilic (contact angle less than 10°) with a short response time. The rate of wetting transition and the desired contact angle can be precisely controlled by modula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 84 publications
2
22
0
Order By: Relevance
“…In contrast to more complex and expensive approaches followed in the literature 2934 , we demonstrate a simple and cost-effective approach to convert a superhydrophobic surface into a superhydrophilic surface. The superhydrophobic surface thus prepared when subjected to oxygen plasma 36 develops -OH bonds on the surface thus gets transformed into a superhydrophilic surface (with WCA < 1°).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to more complex and expensive approaches followed in the literature 2934 , we demonstrate a simple and cost-effective approach to convert a superhydrophobic surface into a superhydrophilic surface. The superhydrophobic surface thus prepared when subjected to oxygen plasma 36 develops -OH bonds on the surface thus gets transformed into a superhydrophilic surface (with WCA < 1°).…”
Section: Introductionmentioning
confidence: 99%
“…Until now, several techniques, such as calcination 26,27 , sol-gel self-assembly 13 , spray coating, layer-by-layer assembly 17 , electrochemical anodization 28 , electrospinning, solution coating, etching, interfacial polymerization and hydrothermal treatment, have been developed for the fabrication of superhydrophilic surfaces by changing the surface chemistry to reduce surface energy and topography for increasing roughness. Similarly, different techniques have been developed for converting superhydrophobic surfaces to superhydrophilic surfaces, such as electrochemical alteration of the oxidation 29 , graphene interface 30 , nano-coating 31 , UV exposure 32 , phase separation and vapour deposition 33 . Recently, fabrication and characterization of a PDMS – derived candle soot coated superhydrophobic surface was reported 34 .…”
Section: Introductionmentioning
confidence: 99%
“…According to the basic principle of Kelvin probe force microscopy, in the uncharged area, the surface potentials fluctuate significantly and result in random data, whereas in the charged area, the surface potentials remain steady. As we have known, the electrowetting phenomenon caused by electric-field-driven solid–liquid interfacial charges will change the wettability from hydrophobic to very hydrophilic [1927]. We thought that the charges injected and accumulated on the solid surface by a direct-current electric field may also change the surface wettability.…”
Section: Resultsmentioning
confidence: 99%
“…The maximum contact angle decreased from 150 ± 0.1° to 20° and the contact-angle saturation conditions changed with droplet size. Zahiri et al [27] reported the reversible active control of surface wettability of copper electrodeposition by an electrochemical process. The surface wettability could be controlled from superhydrophobic to superhydrophilic.…”
Section: Introductionmentioning
confidence: 99%
“…Superhydrophobic surfaces are generally defined as those that display contact angles (CA) greater than 1508 8.Inthe past decades,numerous efforts have been made to understand the superhydrophobic phenomenon in nature (namely,l otus leaves,e lytra of desert beetles,a nd gecko feet), and to develop avariety of artificial superhydrophobic surfaces. [1] In the artificial superhydrophobic surfaces,some rough-textured semiconductor oxide materials, [2] such as ZnO,T iO 2 ,S nO 2 , Fe 2 O 3 ,CuO,and In 2 O 3 ,have received considerable attention owing to their superior functional properties and desired wettability.T his offers great promise for advanced applications including electro-or photo-controllable water permeation, [3] superhydrophobic antibacterial materials, [4] waterresistant electronic devices, [5] and self-cleaning solar cells. [2a, 6] It is well-known that the superhydrophobic behavior of as olid surface is realized either by constructing ar oughtextured surface on ah ydrophobic material or by modifying ar ough surface with hydrophobic organic coatings.M any hypotheses,including the representative Wenzel and Cassie-Baxter models,have been proposed to describe the impact of surface roughness on the wettability.…”
Section: Introductionmentioning
confidence: 99%